Report on technical instruction in Germany : special schools and courses for mechanical engineering and electro-technics - Grande-Bretagne. Foreign Office
tabl. "Presented to both Houses of Parliament by command of His Majesty, January, 1904". - Antériorité : "Reference to previous reports, miscellaneous series n° 540, 561, 566..."